2002
DOI: 10.1179/096805102125000065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in biosynthesis of <I>Actinobacillus pleuropneumoniae</I> serotype 1 O-antigen and biological properties of rough mutants

Abstract: Actinobacillus pleuropneumoniae is an important pathogen of swine. Lipopolysaccharide (LPS) has been identified as the major adhesin of A. pleuropneumoniae and it is involved in adherence to porcine respiratory tract cells. We previously generated seven rough LPS mutants of A. pleuropneumoniae serotype 1 by using a mini-Tn10 transposon mutagenesis system [Rioux S, Galarneau C, Harel J et al. Isolation and characterization of mini-Tn10 lipopolysaccharide mutants of Actinobacillus pleuropneumoniae serotype 1. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The samples were purified on a Bio-Gel P-2 column as described previously (12). Core fractions (fractions 19 -24) eluting off the column slightly after the O-chain (fractions [15][16][17] were combined and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The samples were purified on a Bio-Gel P-2 column as described previously (12). Core fractions (fractions 19 -24) eluting off the column slightly after the O-chain (fractions [15][16][17] were combined and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of the surface properties of these LPS mutants demonstrated that O-antigen deletions in rough mutants have no effect on the adhesion of the bacteria to frozen tracheal sections of pigs, whereas an intact core oligosaccharide region seems to be required for optimal adherence (7,13). Most interestingly, in vivo experiments in pigs showed that the core LPS mutant 5.1 that still produces an O-antigen was less virulent, whereas no difference was observed between the rough mutant 27.1 lacking O-antigen and the parent strain (13)(14)(15). These observations suggest that the LPS core oligosaccharide could play a major role in colonization and pathogenesis of A. pleuropneumoniae in pigs.…”
mentioning
confidence: 96%
See 3 more Smart Citations